Fiber type characterization in skeletal muscle by diffusion tensor imaging. (4th April 2013) - Scheel, Michael; von Roth, Philipp; Winkler, Tobias; Arampatzis, Adamantios; Prokscha, Torben; Hamm, Bernd; Diederichs, Gerd
Abstract : Fiber type distribution within a skeletal muscle, i.e. the quantification of the relative amount of type 1 (slow‐twitching) and type 2 (fast‐twitching) muscle fibers, is of great interest for the monitoring of the effects of training or the treatment of muscle diseases. The purpose of this study was to determine the feasibility of diffusion tensor imaging (DTI) as a tool for noninvasive fiber type quantification in human skeletal muscle. The right calves of 12 healthy volunteers were examined using DTI at 1.5 T. Standard DTI parameters, including fractional anisotropy (FA), and mean, radial and parallel diffusivity (MD, RD and PD, respectively), were determined in the soleus muscle. Fiber type proportion and mean fiber diameter within the soleus muscle were quantified from tissue specimens obtained via a fine needle biopsy. Linear regression analysis tested for associations between DTI and biopsy results. FA values were correlated significantly with fiber type proportion, such that higher FA values indicated a higher proportion of type 1 fibers ( R 2  = 0.5, p  = 0.01). This was based on lower diffusivity perpendicular to the main axis of the fiber in subjects with a higher type 1 fiber proportion (RD: R 2  = 0.52, p  = 0.008). MD was also correlated with the proportion of type 1 fibers ( R 2  = 0.37, p  = 0.037), whereas PD showed no significant correlation. DTI is a promising method for the noninvasive estimation of fiber type proportion in skeletal muscle. This technique may be used to monitor training effects or may be further developed as a biomarker in certain muscle diseases. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : Diffusion tensor imaging is a method for the noninvasive estimation of fiber type proportion in skeletal muscle. Fractional anisotropy values are correlated significantly with fiber type proportion, such that higher values indicate a higher proportion of type 1 fibers ( R 2  = 0.5, p  = 0.01). This is based on lower diffusivity perpendicular to the main axis of the fiber in subjects with a higher type 1 fiber proportion ( R 2  = 0.52, p  = 0.008).